2018
DOI: 10.1186/s13071-018-3094-z
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assessment of the anti-feeding effect for up to 12 months of a slow release deltamethrin collar (Scalibor®) against the sand fly Phlebotomus perniciosus in dogs

Abstract: BackgroundLeishmaniosis/leishmaniasis consists of a wide group of diseases, caused by different Leishmania species and having different hosts. Leishmaniosis caused by Leishmania infantum, a disease primarily of dogs and humans, occurs after susceptible hosts are exposed to the feeding behavior of infected sand flies. A one-year laboratory study in dogs was designed to determine the 364-day anti-feeding efficacy of a slow release deltamethrin collar against the sand fly P. perniciosus, a common host of L. infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Scalibor collars release deltamethrin into dermal secretions, resulting in reduced sand fly blood–feeding by >90%, and increased mortality in blood–fed sand flies by 35%–100% over 8 months[ 25 , 26 ]. More recent studies suggest that Scalibor collars offer 94–98% protection against Phlebotomous perniciosus sand fly bites for up to 12 months[ 49 ]. These effects reduce the likelihood of a collared dog acquiring infection and being a source for onward transmission, thus, they are expected to reduce the number of infectious bites on humans.…”
Section: Discussionmentioning
confidence: 99%
“…Scalibor collars release deltamethrin into dermal secretions, resulting in reduced sand fly blood–feeding by >90%, and increased mortality in blood–fed sand flies by 35%–100% over 8 months[ 25 , 26 ]. More recent studies suggest that Scalibor collars offer 94–98% protection against Phlebotomous perniciosus sand fly bites for up to 12 months[ 49 ]. These effects reduce the likelihood of a collared dog acquiring infection and being a source for onward transmission, thus, they are expected to reduce the number of infectious bites on humans.…”
Section: Discussionmentioning
confidence: 99%
“…The veterinary team fitted and replaced any lost collars, promoted their correct use to dog owners, and recorded any adverse reactions and reasons for collar losses. Scalibor collars have an activity period of 5–6 months against sand flies according to the product label, though longer durations of >10 months are experimentally demonstrated[3537]. Collars were routinely replaced on 5 occasions at an average interval of 182 (S.D.…”
Section: Methodsmentioning
confidence: 99%
“…For decades, the public health authorities have attempted to reduce the incidence of VL through the mass elimination of seropositive dogs, with no apparent success. The available scientific data support the community-wide use of insecticide-impregnated collars, rather than vaccination, to reduce the risk of infection in dogs and humans (Gavgani et al, 2002;Brianti et al, 2014Brianti et al, , 2016Paulin et al, 2018;Courtenay et al, 2019). This conclusion is supported by others.…”
Section: Discussionmentioning
confidence: 57%
“…That study showed Seresto ® to prevent 88.3% incident canine infections compared to 61.8% by Scalibor ® (Brianti et al, 2016). Moreover, Seresto ® provide 8 months of protection against sand flies, whereas for Scalibor ® is labelled for 4 months in Brazil and 5 months in Europe, though a recent laboratory study demonstrated a sustained anti-feeding efficacy of >94% for 12 months against Phlebotomus perniciosus (Paulin et al, 2018). As a follow up consequence of this study, the Ministry of Health of Italy authorized the extension of the label recommendation of Scalibor ® for 12 months (Ministero della Salute, 2018).…”
Section: Can Insecticide-impregnated Collars Protect Dogs From L Infmentioning
confidence: 99%